(Digital) neo-colonialism in the smart city. Issue 12 (2nd December 2021) - Mouton, Morgan; Burns, Ryan
ABSTRACT: The critical research agenda on smart cities has become increasingly interested in the political–economic relations between digital technologies and everyday urban life. It is now clear that in the smart city, quotidian activities have become valorized as data, and are produced, extracted and circulated with little, if any, remuneration to those individuals from whom they have been abstracted. Smart-city scholars often call this process 'digital colonialism' to highlight the uneven relations of power that enable processes of dispossession and profit generation. In this article we argue that greater conceptual clarity is needed around digital colonialism. Specifically, what is called 'digital colonialism' often entails processes more characteristic of neo-colonialism. By teasing out the differences between digital colonialism and digital neo-colonialism, different relations and processes are illuminated, allowing us to theorize the smart city with greater nuance. Here, we focus on the epistemological claims, practices of legibility and repercussions that emerge when focusing attention on the latter. We show that digital neo-colonialism also requires different political strategies of resistance than its colonial counterpart, and we grapple with the multiple ways in which digital technology research has formulated resistance strategies. We advocate for a collective, structural shift in how data and digital technologies are deployed and circulated within the smart city. To substantiate these claims, we draw on a long-term, ongoing database ethnography in Calgary, Alberta, Canada.